Human Resource Accounting : An Effective Strategy for Human Assets Control - Hemamalini, P. H.; Anitha, R.; Devasenathipathi, T. (Prabandhan: Indian Journal of Management, 2011)
Through the nineteenth and the middle of the twentieth century, the need for cost accounting had gained popularity among the industries as they made heavy investments in factories, natural resources and equipment. There was a global transition from manufacturing to service based economies. During 1960s, managerial accounting was basically cost accounting. Due to the augmentation of service industry and expansion of financial institutions, managerial accounting began to mean more than just cost accounting. Subsequently, researchers felt the importance of behavioral accounting. During the same time, human resource accounting also began to emerge.For example in an IT firm, the value of its physical assets is negligible when compared with the value of the knowledge and skills of its personnel. It was found to be similar in case of hospitals, academic institutions, consulting firms etc. The humans were recognized as the integral part of the total worth of an organization, as the success of the organization was contingent on the quality of their Human Resource- its knowledge, skills, competence, motivation and understanding of the organizational culture. As Organizations, particularly in USA are booming to be successful in the implementation of HRA approach, our country too can implement HRA successfully to generate monetary and non-monetary information about human beings in the organizations, on their managerial talents, whose dearth is felt by business organizations.